Tectono-magmatic evolution of Late Jurassic to Early Cretaceous granitoids in the west central Lhasa subterrane, Tibet - Cao, M.; Qin, K.; Li, G.; Li, J.; Zhao, J.; Evans, Noreen; Hollings, P. (Elsevier BV, 2016)
There is ongoing debate as to the subduction direction of the Bangong–Nujiang Ocean during the Mesozoic (northward, southward or bidirectional subduction). Arc-related intermediate to felsic intrusions could mark the location of the subduction zone and, more importantly, elucidate the dominant geodynamic processes. We report whole rock geochemical and zircon U–Pb and Hf isotopic data for granitoids from the west central Lhasa subterrane (E80° to E86°). All rocks show metaluminous to peraluminous, calc-alkaline signatures, with strong depletion of Nb, Ta and Ti, enrichment of large ion lithophile elements (e.g., Cs, Rb, K), a negative correlation between SiO2 and P2O5, and a positive correlation between Rb and Th. All these features are indicative of I-type arc magmatism. New zircon U–Pb results, together with data from the literature, indicate continuous magmatism from the Late Jurassic to the Early Cretaceous (160 to 130 Ma). Zircon U–Pb ages for samples from the northern part of the west central Lhasa subterrane (E80° to E82°30′) yielded formation ages of 165 to 150 Ma, whereas ages of 142 to 130 Ma were obtained on samples from the south. This suggests flat or low-angle subduction of the Bangong–Nujiang Ocean, consistent with a slight southward decrease in zircon εHf(t) values for Late Jurassic rocks.Considering the crustal shortening, the distance from the Bangong–Nujiang suture zone, and a typical subduction zone melting depth of ~ 100 km, the subduction angle was less than 14° for Late Jurassic magmatism in the central Lhasa interior, consistent with flat or low-angle subduction. Compared with Late Jurassic rocks (main εHf(t) values of − 16 to − 7), Early Cretaceous rocks (145 to 130 Ma) show markedly higher εHf(t) values (mainly − 8 to 0), possibly indicating slab roll-back, likely caused by slab foundering or break-off. Combined with previously published works on arc magmatism in the central Lhasa and west part of the southern Qiangtang subterranes, our results support the bidirectional subduction of the Bangong–Nujiang Ocean along the Bangong–Nujiang Suture Zone, and indicates flat or low-angle southward subduction (165 to 145 Ma) followed by slab roll-back (145 to 130 Ma).